2021
DOI: 10.1021/acs.langmuir.1c02254
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Hydrophilic Low-Friction Poly(hydroxyethyl methacrylate) Coating on Silicon Rubber

Abstract: Silicon rubber has been widely used in the biomedical field due to its excellent mechanical properties and physiological inertia. However, the hydrophobic properties of silicon rubber surfaces limit their further application. Therefore, constructing a silicon rubber coating with hydrophilic and low-friction surface properties would be highly significant. Existing methods to achieve such coatings, including grafting polymer brushes and the deposition of hydrophilic materials, suffer from several deficiencies su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The main chain of the PDMS structure is alternately connected by silicon and oxygen, and the side chain is composed of methyl groups. 38 The peaks at 800, 1260 � , and 2960 cm −1 are attributed to Si−CH 3 stretching vibration absorption, Si−CH 3 twisting deformation vibration absorption, and CH 3 asymmetric stretching vibration absorption, respectively, and the peak at 1020 and 1074 cm −1 attributed to the asymmetric stretching of Si−O−Si (Figure 1A). 43 The stretch vibration absorption peaks of −OH and −NH appear on the PDA coating and PDA/PAA coating surface at 3380 and 1620 cm −1 (Figure 1B), and they are not found on the PDMS surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main chain of the PDMS structure is alternately connected by silicon and oxygen, and the side chain is composed of methyl groups. 38 The peaks at 800, 1260 � , and 2960 cm −1 are attributed to Si−CH 3 stretching vibration absorption, Si−CH 3 twisting deformation vibration absorption, and CH 3 asymmetric stretching vibration absorption, respectively, and the peak at 1020 and 1074 cm −1 attributed to the asymmetric stretching of Si−O−Si (Figure 1A). 43 The stretch vibration absorption peaks of −OH and −NH appear on the PDA coating and PDA/PAA coating surface at 3380 and 1620 cm −1 (Figure 1B), and they are not found on the PDMS surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure A,B shows the infrared spectrum of the surface of original PDMS, PDA coating, and PDA/PAA coating. The main chain of the PDMS structure is alternately connected by silicon and oxygen, and the side chain is composed of methyl groups . The peaks at 800, 1260  , and 2960 cm –1 are attributed to Si–CH 3 stretching vibration absorption, Si–CH 3 twisting deformation vibration absorption, and CH 3 asymmetric stretching vibration absorption, respectively, and the peak at 1020 and 1074 cm –1 attributed to the asymmetric stretching of Si–O–Si (Figure A) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several surface modification methods of polymeric materials have been employed to enhance lubrication between implanted biomedical devices and soft tissues. Among different modification strategies, the application of a lubrication coating on the surface can efficiently reduce the friction associated with biomedical devices. For example, Peng et al reported the development of a multifunctional zwitterionic coating made by sulfobetaine/active ester block copolymers via controlled reversible addition–fragmentation chain transfer polymerization, which could be covalently grafted on the surface of silicone rubber and lead to improved lubrication.…”
Section: Introductionmentioning
confidence: 99%